Denaturing gradient gel electrophoresis characterisation of microbial communities in polycyclic aromatic hydrocarbon and polychlorinated biphenyl contaminated soil - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Thesis (PhD (Microbiology))--University of Pretoria, 2007.